НЕФТЕПЕРЕРАБОТКА И ГАЗОХИМИЯ КАК ПРИОРИТЕТЫ ИННОВАЦИОННОГО РАЗВИТИЯ ЭКОНОМИКИ НЕФТЕГАЗОВЫХ РЕГИОНОВ КАЗАХСТАНА - O. I. Egorov; G. D. Amaniyazova; B. S. Saubetova (Экономика: стратегия и практика)
One of the directions of development that can improve the efficiency and competitiveness of the functioning of Kazakhstan’s oil and gas industry is restructuring. Due to the restructuring, the share of the downstream in the overall structure of industrial production and salable production with a high share of value added can be significantly increased.Such direction of development will result in balance in use of hydrocarbonic resources that will allow to define specific needs for initial raw materials of oil and petrochemical complexes, volumes of export deliveries. The solution of the problem of balance of volumes of production, export and the processing of hydrocarbonic raw materials considering its qualitative parameters will play the positive role in change of structure of industrial production towards increase in a share of the downstream.